2017
DOI: 10.1140/epjp/i2017-11696-0
|View full text |Cite
|
Sign up to set email alerts
|

Hamilton-Jacobi analysis of the four-dimensional BF model with cosmological term

Abstract: In this work we perform the Hamilton-Jacobi constraint analysis of the four dimensional Background Field (BF ) model with cosmological term. We obtain the complete set of involutive Hamiltonians that guarantee the integrability of the system and identify the reduced phase space. From the fundamental differential we recover the equations of motion and obtain the generators of the gauge and shift transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Besides, within the multisymplectic approach, we also constructed the generator of the slicing on the multimomenta phase-space of the theory. In particular, we showed at the multiisymplectic level that the superposition of the covariant momentum maps associated to the gauge and topological symmetries of the BF theory projects into the instantaneous phase-space generator of infinitesimal gauge transformations of the system and, and we also realized that the zero level set of the above projected momentum map coincides with the surface on the instantaneous phase-space defined by the first class constraints of the non-Abelian topological BF field theory, which arise within the Dirac-Hamiltoniana analysis of the model as described in [10,14]. Furthermore, we found that since the generator of the slicing on the multimomenta phase-space generates covariant canonical transformations, its associated covariant momentum map projects to the extended Hamiltonian of this topological field theory also obtained by means of the Dirac's algorithm in the instantaneous canonical analysis [14].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Besides, within the multisymplectic approach, we also constructed the generator of the slicing on the multimomenta phase-space of the theory. In particular, we showed at the multiisymplectic level that the superposition of the covariant momentum maps associated to the gauge and topological symmetries of the BF theory projects into the instantaneous phase-space generator of infinitesimal gauge transformations of the system and, and we also realized that the zero level set of the above projected momentum map coincides with the surface on the instantaneous phase-space defined by the first class constraints of the non-Abelian topological BF field theory, which arise within the Dirac-Hamiltoniana analysis of the model as described in [10,14]. Furthermore, we found that since the generator of the slicing on the multimomenta phase-space generates covariant canonical transformations, its associated covariant momentum map projects to the extended Hamiltonian of this topological field theory also obtained by means of the Dirac's algorithm in the instantaneous canonical analysis [14].…”
Section: Discussionmentioning
confidence: 64%
“…Besides, we also construct the covariant momentum maps associated to the BF model. Finally, following the works developed in [16,18,21,22,26], after performing the space plus time decomposition for the BF theory, we are able to recover not only the extended Hamiltonian, but also the generator of the infinitesimal gauge transformations as well as the first and second class constraints of the non-Abelian topological BF theory, which explicitly correspond to the results obtained by means of the Dirac's algorithm in references [10,14].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Let us start with a brief review of the relevant properties of BF theory [22][23][24][25][26][27][28][29], a topological field theory formulated on the principal bundle of a group G over the spacetime manifold M . In this principal bundle we can define a connection A and the corresponding curvature, a 2-form F .…”
Section: A Constructing the Actionmentioning
confidence: 99%
“…The identification of noninvolutive Hamiltonians allows us to construct the so-called generalized brackets which are a generalization of the Poisson brackets, at the end of the procedure the fundamental differential will be expressed in terms of involutive Hamiltonians and the generalized brackets. The HJ method has been applied for studying several gauge systems, in particular systems with general covariance just like BF theories [23,24], topological invariants [25] and field theories [26,27]. In this respect, it has been showed that the development of the HJ scheme is more economical with respect either Dirac or the FJ approaches.…”
Section: Introductionmentioning
confidence: 99%